2011
DOI: 10.1007/s11483-011-9229-9
|View full text |Cite
|
Sign up to set email alerts
|

The Optical Absorption Coefficient of Maize Seeds Investigated by Photoacoustic Spectroscopy

Abstract: The knowledge about a seed's optical parameters is of great relevance in the seed technology practice. Such parameters provide information about its absorption and reflectance, which in turn is related to its color, quality, and health condition. The objective of the present study was to determine the optical absorption coefficient β for maize seeds (Zea mays L.) by means of the photoacoustic spectroscopy (PAS). Untreated seeds (I) and seeds dyed with methyl red (II) were used in this investigation. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
(19 reference statements)
0
4
0
2
Order By: Relevance
“…Validation of the photoacoustic spectroscopy technique to characterize biological samples, such as corn seeds, and compared with spectra obtained by UV–Vis spectroscopy with an integrating sphere, demonstrated the usefulness of the photoacoustic spectroscopy technique to characterize foodstuffs such as corn kernels ( Hernandez-Aguilar et al, 2011 ). In this way, it is effectively a reliable method, reported in the scientific literature, although this contribution is intended to give an idea of the possibility of using it for other applications in the foodstuff area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation of the photoacoustic spectroscopy technique to characterize biological samples, such as corn seeds, and compared with spectra obtained by UV–Vis spectroscopy with an integrating sphere, demonstrated the usefulness of the photoacoustic spectroscopy technique to characterize foodstuffs such as corn kernels ( Hernandez-Aguilar et al, 2011 ). In this way, it is effectively a reliable method, reported in the scientific literature, although this contribution is intended to give an idea of the possibility of using it for other applications in the foodstuff area.…”
Section: Resultsmentioning
confidence: 99%
“…In case of characterizing solid samples, UV-VIS spectroscopy with integrating sphere should be used. Hernandez-Aguilar et al (2011) reported the reflectance spectra, from 620 nm to 700 nm wavelength of different layers of corn, obtained by UV-VIS spectroscopy with integrating sphere. In the present study photoacoustic spectroscopy is proposed to qualitatively observe the changes in the absorption bands, corresponding to secondary metabolites contained in moringa bread.…”
Section: Introductionmentioning
confidence: 99%
“…Among the several techniques to characterize different materials, ranging from homogeneous to non-homogeneous ones, the photothermal techniques (PT) stand out because are nondestructive. One of the PT techniques is the photoacoustic spectroscopy (PAS), used to study the optical and reflectance properties in different areas of knowledge, obtaining optical properties in biological materials, having relation to color, quality and state of degradation [9][10][11]. By using PT techniques, different crops such as wheat, acai, and corn seeds have been studied to obtain various optical and thermal properties [9,10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, a lo largo de los años, la Espectroscopia Fotoacústica (EFA), ha mostrado su potencial en las áreas biomédicas [9] , debido a que es una técnica no destructiva que requiere una pequeña cantidad de la sustancia en estudio y que factores ópti-cos que limitan la espectroscopia en materiales bioló-gicos, tales como la dispersión de la luz, no son impedimento en la EFA para la investigación óptica de dichas muestras. La validación de la técnica de EFA al compararla con otras técnicas convencionales como es el caso de espectroscopia UV-Vis se ha realizado en otros estudios, de tal manera los datos obtenidos serían inversos a los obtenidos en reflectancia para muestras opacas [10] . Dentro de las ventajas que presenta la EFA se encuentra que la transmitancia y dispersión de la luz incidente a través de la muestra analizada no limita su aplicación al estudio de propiedades ópticas en el área biológica.…”
Section: Introductionunclassified